A structural equation modelling approach to validate the dimensions of SERVPERF in airline industry of Malaysia - Abdullah, Kalthom; Jan, Muhammad Tahir; Abd. Manaf, Noor Hazilah (Society For Science And Nature (SFSN), 2012)
perspectives of Malaysian passengers by replicating the factors used in an earlier study by Cronin and Taylor and to address the implication of culture on their choice.